Dyspareunia and Childbirth. Issue 5 (May 2015) - McDonald, E. A.; Gartland, D.; Small, R.; Brown, S. J.
<x xml:space="preserve">Abstract</x> ABSTRACT Almost all women experience dyspareunia during the first sexual intercourse following childbirth. The relationship between mode of delivery, perineal trauma, and other obstetric risk factors is poorly understood. Previous studies examining this relationship lacked long-term follow-up data and have a number of other methodological limitations. The aim of this multicenter, prospective cohort study was to investigate the relationship between obstetric risk factors, including mode of delivery and perineal trauma, and postpartum dyspareunia. A total of 1507 nulliparous women, older than 18 years, who were in the first and second trimesters of pregnancy were recruited between April 2003 and December 2005 at 6 maternity hospitals in Melbourne, Australia. Data were obtained from questionnaires completed by participants at baseline and at 3, 6, 12 and 18 months postpartum. Univariable and multivariable logistic regression were used to evaluate risk factors for postpartum dyspareunia; data were adjusted for maternal age and other potential confounders. Patient-reported dyspareunia at 18 months postpartum was the primary study outcome measure. A total of 1244 women (83%) completed the baseline and all 4 postpartum questionnaires; 78% resumed vaginal intercourse by 3 months postpartum, 94% by 6 months, and 98% by 18 months. Dyspareunia was reported by 45% of the women at 3 months postpartum and 28% at 12 months; dyspareunia persisted in 23% of the women at 18 months postpartum. The adjusted odds ratio (aOR) for dyspareunia at 18 months postpartum was significantly higher in women who gave birth by emergency cesarean delivery (2.41; 95% confidence interval [CI], 1.4–4.0; P = 0.001), by vacuum extraction (2.28; 95% CI, 1.3–4.1; P = 0.005) or by elective cesarean delivery (1.71; 95% CI, 0.9–3.2; P = 0.087) compared with women who had a spontaneous vaginal birth with an intact perineum or unsutured tear. This study indicates that obstetric intervention is associated with persisting dyspareunia in a significant proportion of women up to 18 months postpartum. Important questions are raised about the longer-term impact of operative procedures on postpartum maternal morbidities. The data demonstrate the need to focus clinical attention on ways to prevent postpartum morbidity whenever possible.